Harnessing the Power of Social Media to Obtain Biodiversity Data About Cetaceans in a Poorly Monitored Area - Morais, Pedro; Afonso, Luís; Dias, Ester (Frontiers in Marine Science, 2021)
The study and conservation of cetaceans benefit from systematic studies and non-systematic records about sightings and strandings. However, iEcology (internet ecology) was critical for numerous ecological studies and should be in the toolkit of cetacean ecologists. We hypothesize that iEcology is irreplaceable to obtain diversity data about cetaceans in poorly monitored regions that coincide with touristic destinations, where whale-watching companies go out to sea regularly and post their sightings on social media. Our study assessed the advantages and disadvantages of iEcology while obtaining the first broadscale and long-term assessment about cetaceans’ diversity off the Algarve, a European tourist destination with numerous whale-watching companies. We retrieved 1,299 time-referenced records about 15 species posted on Facebook and Instagram between 2011 and 2020. Data collected from Biodiversity4All, an online citizen science biodiversity database, disclosed georeferenced records about nine species made between 2008 and 2020, however, the number of records was 15.8 times lower than social media posts. We obtained information about 16 species, two of which were never mentioned in the scientific literature [Balaenoptera musculus, Balaenoptera edeni (record made in 2021)] and five species were only mentioned in the gray literature. Previous assessments were restricted in time, published in the gray literature, and only reported six and 11 species. So, social media was essential to obtain the first broadscale and long-term assessment of cetaceans’ diversity off the Algarve. The main advantages of iEcology were the possibility to obtain data collected over one decade and its low cost. The main disadvantages are the impossibility to obtain georeferenced records from social media, the difficulty to estimate the number of individuals in large groups, and the presence of rare species can be inflated if multiple whale-watching companies report the same individual(s) while they migrate along the coast. Nonetheless, these disadvantages can be mitigated. Overall, we endorse the use of iEcology to increase the ecological knowledge about cetaceans which might be the only tool to study them in numerous regions across the world. The contributions of whale-watching companies are invaluable, so we recommend the implementation of a standardized cetacean observation log as a relevant source of data for conservation.